A Field Key to the Deciduous Trees of Anshi National Park - Kulkarni, Satish S.; Hegde, Ganesh R.; Bhat, Pradeep (Indian Forester, 2015)
A field key to the 30 deciduous trees of Western Ghats, in Anshi National Park (ANP), situated in Uttara Kannada district, Karnataka is prepared, based on vegetative characters such as leaf arrangements, their nature, etc. These are dependable characters and are used for preparing the key.